Sex and income level can be determinants for meat attachment behavior among Turkish university students - Gunalan, Eif; Parmaksiz, Ayhan; Mutlu, Hayrettin (The North African Journal of Food and Nutrition Research, 2024)
Background: The Meat Attachment Questionnaire (MAQ) is a scale to measure the positive bond in meat consumption. Aims: This study aimed to validate and assess reliability of the Turkish version of the MAQ and to explore its relationship with various factors, including sociodemographic characteristics, meat consumption habits, and subscales of the Green Eating Survey (GES). Subjects and Methods: The study was carried out with 214 university students. Participants completed the MAQ, the Food Frequency Questionnaire, and the GES. Statistical analyses including item analysis, Cronbach’s alpha, intraclass correlation coefficient test - retest reliability, one-way ANOVA, Welch ANOVA, t-test, Pearson’s correlation, and post hoc tests (Tukey’s HSD and Games-Howell), were performed using SPSS (version 26). Confirmatory factor analysis (CFA) was conducted with the lavaan (version 0.6 – 13) and semPlot (version 1.1.6) R packages. Results: All factor loadings were statistically significant, and high fit indices were obtained for the model tested in the second-order CFA model. (χ2/df = 151,93/101 = 1.50; RMSEA = 0.05; SRMR = 0.08; NFI = 0.97; NNFI = 0.99; CFI = 0.99; GFI = 0.98; AGFI = 0.97). Significant differences were found in several MAQ subscale scores: hedonism, entitlement, dependence, and global scores were higher among men (p < 0.05). The entitlement score was significantly higher in the “income < expenses “group compared to the “income = expenses “group (p < 0.05). Participants with higher red meat and poultry consumption exhibited significantly higher hedonism, dependence, and global MAQ scores (p < 0.05). Conclusions: The Turkish version of the MAQ can be accepted as a reliable and valid scale for use among university students. While factors such as sex, income level, and meat consumption appear to influence MAQ scores, body mass index and green eating behaviors do not have a direct effect. Keywords: Green eating, meat, reliability, sustainability, validity.